Strategies in Minimizing Dependency on Foreign Workers in Malaysian Construction Industry - Lim, Cai Xuan (2021)
The Malaysian construction industry contributes significantly to the country's economic growth as well as the development of social and economic buildings. Majority of the construction companies prefer to hire foreign labour due to the easy employment and low wages rate as well as the unpleasant working environment (3D - Dirty, Dangerous, and Difficult) that local workers find undesirable. As a result, the number of migrant workers has gradually increased. Indeed, the influx of migrant workers has undeniably caused negative impacts to human health, such as malaria and COVID-19, as well as political and social problems. These shortcomings have influenced our country's economic development. As a result, this paper intends to determine the strategies in minimizing the dependency on foreign labours in the Malaysian construction industry by identifying the factors as well as the negative impact induced by foreign labours. This study focuses only on the general opinions of the registered construction firms in Kuala Lumpur. The opinions of respondents were gathered from questionnaire surveys and phone interviews to provide a more comprehensive analysis of the current situation of reliance level on foreign labours. It was found that one of the negative impacts that agreed by most of the respondents is affecting the level of productivity due to insufficient expertise of foreign labours. According to the results, all the strategies listed are viable, but stronger agreements are seen on the allocation of incentive to import work-saving technologies with the aid of the Government. Also, the results obtained had certain validity which makes strategies workable, as the responses were received from the registered contractors who act as employers to foreign workers. This research enhances the direction for relevant parties such as the Government, CIDB, and IBS-related firms to adopt potential strategies to reduce the dependence on foreign labour. The professional boards have to restructure awareness campaigns into the form of comprehensive awareness programmes and exhibits of best practice for IBS to be recognized and widely used.